Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/ptr.7735
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lipid metabolism with natural products: A novel strategy for gastrointestinal cancer therapy

Abstract: Gastrointestinal cancer (GIC), including gastric cancer and colorectal cancer, is a common malignant tumor originating from gastrointestinal epithelial cells. Although the pathogenesis of GIC remains unclear, aberrant lipid metabolism has emerged as a hallmark of cancer. Several enzymes, proteins, and transcription factors are involved in lipid metabolism reprogramming in GIC, and their abnormal expression can promote lipid synthesis and accumulation of lipid droplets through numerous mechanisms, thereby affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…Through inflammatory reactions, abnormalities in lipid metabolism may contribute to the growth of stomach cancer. Abnormal lipid metabolism can activate inflammatory cells and release inflammatory factors, thereby exerting an influence on the development of GC [ 25 , 43 ]. Recent studies have employed LMRGs to create novel predictive models for a variety of tumor types, including papillary thyroid cancer, colon adenocarcinoma, and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through inflammatory reactions, abnormalities in lipid metabolism may contribute to the growth of stomach cancer. Abnormal lipid metabolism can activate inflammatory cells and release inflammatory factors, thereby exerting an influence on the development of GC [ 25 , 43 ]. Recent studies have employed LMRGs to create novel predictive models for a variety of tumor types, including papillary thyroid cancer, colon adenocarcinoma, and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Specific lipid molecules, including phosphatidylinositol, fatty acids, and cholesterol metabolites, also regulate signaling pathways linked to tumor growth, invasion, and metastasis. Furthermore, the involvement of lipid metabolism in drug resistance poses a significant challenge in treating GC [ 23 25 ]. It was reported that reprogrammed lipid metabolism allows GC cells to use lipids as an energy source, supporting their rapid growth and division.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids are a class of basic nitrogen-containing organic compounds found in nature, most of which have complex circular structures. Alkaloids are one of the clinically effective ingredients in the treatment of diseases (Gjorgieva Ackova et al 2023 ; Guo et al 2023 ). Wang et al ( 2018a , b , c , d ) found that evodiamine could upregulate the phosphorylation levels of p38 and JNK in glioblastoma multiforme cells, which led cancer cell apoptosis.…”
Section: Natural Product-targeted Mapk-signaling Pathway For Cancer P...mentioning
confidence: 99%
“…In recent years, accumulated studies have explored the potential of targeting metabolism to in uence cancer progression 9 . Natural products are gaining recognition as a therapeutic modality to modulate metabolic reprogramming and serve as convenient natural remedies 10,11 . Some natural products have been proven to exhibit superior inhibitory effects on cancer progression and have shown promise in mitigating toxic side effects induced by radiotherapy, chemotherapy, or targeted therapies 12 .…”
Section: Introductionmentioning
confidence: 99%